2017
DOI: 10.9755/ejfa.2017-01-240
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physicochemical Characteristics and Composition of Bergamot Oil Seed Extracted From Three Different Cultivars

Abstract: The effect of cultivar on bergamot seed oil composition from three cultivars (Castagnaro, Femminello and Fantastico) grown in province of Reggio Calabria (Southern Italy) was investigated.The maximum oil yield was 35.01 g 100 g-1 in Castagnaro cultivar. The acidity values of the oil varied between 0.62 and 0.87 mg NaOH per g of oil, and peroxide values varied between 11.67 meq/kg and 14.30 meq/kg. The major fatty acid of the extracted seed oils was oleic (31% to 34%), followed by linoleic (27% to 30%) and palm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…The authors observed that lower AV (1.19 g/100 g) and PV (1.22 meqO 2 /kg) were exhibited by ‘Barker’, while the same oxidation indices were higher in ‘Collison’ (2.23 g/100 g) and ‘Fortuna’ (1.41 meqO 2 /kg), respectively. In a related study, Sicari et al. (2017) reported similar findings from the seed oil of bergamot cultivars (‘Castagnaro’, ‘Ferminello’ and ‘Fantastico’).…”
Section: Preharvest Factors Affecting Quality Attributes Of Edible Frsupporting
confidence: 61%
See 3 more Smart Citations
“…The authors observed that lower AV (1.19 g/100 g) and PV (1.22 meqO 2 /kg) were exhibited by ‘Barker’, while the same oxidation indices were higher in ‘Collison’ (2.23 g/100 g) and ‘Fortuna’ (1.41 meqO 2 /kg), respectively. In a related study, Sicari et al. (2017) reported similar findings from the seed oil of bergamot cultivars (‘Castagnaro’, ‘Ferminello’ and ‘Fantastico’).…”
Section: Preharvest Factors Affecting Quality Attributes Of Edible Frsupporting
confidence: 61%
“…In the same study, varying temperature and pressure in subcritical propane extraction of passion seed oil did not significantly affect FFA and AV of the extracted oil. On the contrary, decreasing temperature from 40 to 30 °C and increasing pressure and carbon dioxide flow rate from 150 to 250 bar and 731–919 kg/m 3 , respectively in supercritical fluid extraction of bergamot seed oil doubled the PV ( Sicari et al., 2017 ). Rui et al.…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 96%
See 2 more Smart Citations
“…Studies on the Calabrian olive growing has been conducted since more than 10 years, focused on the qualitative aspects of the olive processing, [20][21][22] and on the quality of olive oils from different varieties produced in Calabria. [23][24][25][26][27][28][29][30][31][32] The aim of this work is to evaluate the effect of the harvesting time of olive drupes to the quality of the obtained monovarietal oils, considering in this study the cultivars more prevailing on the composition of the Calabrian olive oil PGI.…”
Section: Introductionmentioning
confidence: 99%